Inventory of insects groups in Gunung Ledang, Johor, Malaysia - Maryati Mohamed,; David, Maricel C.; Noor Asyikin Mohd Razali,; Fadhil Ahmad Rajini, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2014)
The objective of this study is to find out the viability and potential of insects to be promoted as nature tourism product in Gunung Ledang, Johor, Malaysia. Gunung Ledang is a tourism site and people visit Gunung Ledang to enjoy the mountain ambience, trekking and climbing. To add on to existing tourism packages, a research to study on the potential of another form of nature-based tourism was carried out; which is called Entotourism as it focuses on using insects as an attraction. In this study point count method were used to observed and record all insects and survey questionnaires to find out whether entotourism have potential in Gunung Ledang. Presenting, eight common insects groups are frequently found are: ants, butterflies, termites, dragonflies, moths, beetles, cicadas and damselflies. This paper then discussed how tourists perceived insects. A total of 151 visitors responded to the questionnaires and results showed that 90.1% of tourist found insects as attractive and 88.7% would want to visit insects in a natural habitat. Meanwhile 83.4% agreed that entotourism has potential in Gunung Ledang and 86.8% stated that entotourism could attract international tourists to Malaysia. In addition, 60.9% of tourists are interested in entotourism and 72.2% would want to know more about insects. In this research we have shown that entotourism has potential to be developed at Gunung Ledang.